Seismic Response Reduction of Megaframe with Vibration Control Substructure - Jun-Qi Huang; Xun Chong; Qing Jiang; Xian-Guo Ye; Han-Qin Wang (Shock and Vibration)
Megaframe with vibration control substructure (MFVCS) is a tuned mass damper system, which converts the substructures into the tuned mass. In this study, a kind of MFVCS using both lead-rubber bearings and viscous dampers to connect the vibration control substructure with the megaframe was proposed. Then, based on a validated finite element model, a parametric analysis was conducted to study the effect of two parameters, the tuning frequency (i.e., the frequency of the substructure) and the damping provided by the lead-rubber bearings and viscous dampers on the seismic response reduction of the MFVCS under both frequent and rare earthquakes (i.e., probability of exceedance of 63% and 2% in 50 years, resp.). Furthermore, the optimized values of these two parameters were achieved. The results indicated that (1) the proposed MFVCS could provide a considerable seismic response reduction under frequent earthquake and showed a strong robustness; (2) the optimized values of the frequency ratio (ratio of tuning frequency to the megaframe’s natural frequency) and damping scale factor (ratio between the investigated damping and a standard value) were 0.96 and 1.0, respectively; and (3) the seismic response reduction of the MFVCS under rare earthquake was lower than that under frequent earthquake.